PECULIARITIES OF PROFESSIONAL ORIENTATION OF PEDAGOGUES IN THE CONDITIONS OF POSTGRADUATE EDUCATION - Naumova, Viktoriia (Educological discourse, 2021)
The article is devoted to the experimental verification of personal features of professional orientation of pedagogues in the conditions of postgraduate education. In the course of theoretical analysis of psychological and pedagogical literature it is established that the development of professional orientation of teachers in postgraduate education is closely related to the professional and personal development of the teacher. The objectives of the empirical study were: to select psychodiagnostic techniques and tests that will highlight the features of the professional orientation of teachers; to form a representative sample of teachers; to diagnose respondents, to carry out mathematical processing of the received data; describe the relationship of features that affect the professional orientation of teachers and interpret the results. Experimental work involved the using of exclusively adapted and standardized methods and tests, it contributed to obtaining reliable and valid results that characterize the features of the professional orientation of teachers. It is proved and experimentally confirmed that the main personal features of professional orientation of teachers in postgraduate education should include intrinsic motivation, level of empathy, level of self-esteem, level of social self-control. It was found that the motivational, empathic and evaluative components should be distinguished in the professional orientation of pedagogues. The obtained results of the empirical research testify to the expediency of organizing special psychological and pedagogical work with students of advanced training courses in the conditions of postgraduate pedagogical education, aimed at the development of professional orientation of pedagogues. In the future it is necessary to pay attention to the study of organizational-pedagogical and psychological-pedagogical conditions of interdependence of pedagogical orientation and professional development of a pedagogue.